Smart Village In Strengthening Public Services And Village Economy: A Case Study In Linau Village, Bengkulu - Yuningsih, Siti; Nugraha , Riang Adi; Suzanah , Roro Sosi (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The rapid development of information and communication technology (ICT) has driven significant transformation in governance and public service delivery, including at the village level. The smart village concept emerges as an innovative approach that integrates technology, governance, economic empowerment, and environmental sustainability to address rural development challenges. This study aims to analyze the implementation of the smart village concept in Linau Village, Kaur Regency, Bengkulu, and examine its impact on public services and the local economy. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and documentation, and analyzed using descriptive analysis combined with SWOT analysis. The findings reveal that the implementation of the Smart Fisheries Village (SFV) program in Linau Village has contributed positively to improving service efficiency, transparency, and accessibility. The use of digital technology in fisheries production, processing, and marketing has expanded market access, enhanced product competitiveness, and increased community income. However, the implementation of the smart village concept has not yet been fully optimized due to several challenges, including limited human resource capacity in digital literacy, uneven technological infrastructure, and the lack of integration across digital systems. The SWOT analysis indicates that Linau Village possesses strong internal potential and external opportunities, positioning it in a growth-oriented strategy. Nevertheless, strategic efforts are required to overcome existing weaknesses and mitigate potential threats. Overall, this study concludes that the smart village approach is effective in promoting sustainable rural development. With appropriate strategies such as strengthening digital literacy, improving infrastructure, and fostering multi-stakeholder collaboration, Linau Village has the potential to become a model for smart village development in Bengkulu and other regions with similar characteristics.